1994
DOI: 10.1148/radiology.192.1.8208970
|View full text |Cite
|
Sign up to set email alerts
|

F-18 fluorodeoxyglucose PET in vivo evaluation of pancreatic glucose metabolism for detection of pancreatic cancer.

Abstract: FDG PET has the potential to improve the detection of lymphadenopathy and the differential diagnosis of pancreatic masses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
104
2
5

Year Published

1996
1996
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 204 publications
(116 citation statements)
references
References 0 publications
5
104
2
5
Order By: Relevance
“…Indeed, glucose competes with FDG for transport and a high level of plasma glucose could inhibit FDG uptake within the tumour. Bares suggested this competition to be a possib][e cause of false-negative results, but the four patients with false-negative findings reported by Stollfuss did not have diabetes or elevated glucose levels [163,168]. Evidence of metastatic extension of pancreatic carcinoma, lymph node involvement or liver metastases can be appreciated on PET images.…”
Section: Pancreatic Carcinomamentioning
confidence: 95%
See 2 more Smart Citations
“…Indeed, glucose competes with FDG for transport and a high level of plasma glucose could inhibit FDG uptake within the tumour. Bares suggested this competition to be a possib][e cause of false-negative results, but the four patients with false-negative findings reported by Stollfuss did not have diabetes or elevated glucose levels [163,168]. Evidence of metastatic extension of pancreatic carcinoma, lymph node involvement or liver metastases can be appreciated on PET images.…”
Section: Pancreatic Carcinomamentioning
confidence: 95%
“…Several groups, predominantly from Japan and Germany, have evaluated the role of FDG PET in the differentiation of pancreatic adenocarcinoma from benign chronic pancreatitis and mass-forming pancreatitis [163][164][165][166][167][168][169]. Results indicate a sensitivity of ca.…”
Section: Pancreatic Carcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…We examined various blood tests which possibly influence the uptake of FDG, including blood sugar 27 and CRP 28 , in addition to ordinary blood tests of BUN, creatinine, bilirubin, ALP, amylase, WBC, and CA19-9.…”
Section: Laboratory Testsmentioning
confidence: 99%
“…[7][8][9][10][11] Markedly increased FDG uptake in esophageal squamous cell carcinoma (SCC) has been documented in several studies, [12][13][14][15] and they have reported that PET using FDG shows greater sensitivity in the diagnosis of involved regional lymph nodes than computed tomography (CT). This suggests that PET may have a role in evaluating the stage of esophageal carcinoma.…”
mentioning
confidence: 99%